Impact of ICT usage on indigenous peoples’ quality of life: Evidence from an Asian developing country - Md Mahfuz Ashraf (Australasian Journal of Information Systems, 2015)
Indigenous communities across the world have been suffering disadvantages in several domains, e.g. erosion of land rights, language and other cultural aspects, while at the same time being discriminated against when prepared to integrate into the dominant cultures. It has been argued in the literature that information communication technologies (ICTs) have the potential of contributing to addressing some of these disadvantages – both in terms of rebuilding what has been eroded and facilitating integration into non-Indigenous societies. In trying to understand how ICTs can be useful for these processes, it is important to do so from a conceptual framework that encompasses the multi-dimensionality of the issues faced by Indigenous communities. The conceptual frameworks frequently used in the ICT literature tend to focus on adoption, use and diffusion of technologies rather than how the use of ICTs affects the livelihoods of the users, which is the focus of this paper. The conceptual framework is informed by the capability approach (CA), in particular by the five freedoms identified in the seminal work of Amartya Sen (2001), “Development as Freedom” (DaF). Data were collected from a purposive sample in an Indigenous community in Bangladesh, using a qualitative method to map how ICTs had affected the lives of these community members The findings suggest that the participants perceived that ICTs had made positive contributions, particularly the benefits they gained from learning how to use computers in the domains that are relevant from the perspective of the five freedoms espoused in DaF. The findings reported in this paper are useful for policy formulation in Bangladesh. As the study is contextualised in a transitional economy setting and can therefore not be generalised, but we believe that the conceptual framework has much to offer future research designed to understand how ICTs can improve the livelihoods of Indigenous individuals and communities.